The free moment in running and its relation to joint loading and injury risk. (2nd January 2016) - Willwacher, Steffen; Goetze, Irena; Fischer, Katina Mira; Brüggemann, Gert-Peter
Abstract : The purpose of this study was to explore the relationship between free moment (FM) characteristics, joint mechanics and injury risk, in order to evaluate the potential of the FM as a variable for runner classification into functional groups with similar footwear demands. Lower extremity joint mechanics, ground reaction forces and the FM of 222 male and female injury free runners were analysed using an optoelectric motion capture system and a force plate while running at 3.5 m/s. During a follow-up period of 6 months, runners were reporting any running-related injuries to an experienced orthopaedist. Different FM patterns could be extracted using functional principal component analysis (FPCA). The first two eigenfunctions derived from FPCA were able to predict about 87% of the variance in the data-set and could be related to the two main functions of FM application in straight running -- transversal plane whole body oscillation control and compensation of insufficient transversal moment cancellation. FM patterns differed with respect to lower extremity joint moments and joint kinematics, mostly in the transversal and frontal plane of motion. Runners suffering from patellofemoral pain syndrome showed FM patterns with distinct external rotation components and differed from their matching controls, even though the number of runners, who suffered from injuries were too low to allow valid inferences. In conclusion, it seems that the FM could be useful in the classification of runners into functional groups as it possesses a considerable inter-subject variability, a relationship to the mechanical demands put on lower extremity joints and potentially to injury risk, while being comparably easy to measure.